Effect of Colchicine vs Usual Care Alone on Intubation and 28-Day Mortality in Patients Hospitalized with COVID-19: A Randomized Clinical Trial - Diaz, Rafael (2022)
Importance Hospitalized patients with COVID-19 pneumonia have high rates of morbidity and mortality. Objective To assess the efficacy of colchicine in hospitalized patients with COVID-19 pneumonia. Design, Setting, and Participants The Estudios Clínicos Latino América (ECLA) Population Health Research Institute (PHRI) COLCOVID trial was a multicenter, open-label, randomized clinical trial performed from April 17, 2020, to March 28, 2021, in adults with confirmed or suspected SARS-CoV-2 infection followed for up to 28 days. Participants received colchicine vs usual care if they were hospitalized with COVID-19 symptoms and had severe acute respiratory syndrome or oxygen desaturation. The main exclusion criteria were clear indications or contraindications for colchicine, chronic kidney disease, and negative results on a reverse transcription–polymerase chain reaction test for SARS-CoV-2 before randomization. Data were analyzed from June 20 to July 25, 2021. Interventions Patients were assigned in a 1:1 ratio to usual care or usual care plus colchicine. Colchicine was administered orally in a loading dose of 1.5 mg immediately after randomization, followed by 0.5 mg orally within 2 hours of the initial dose and 0.5 mg orally twice a day for 14 days or discharge, whichever occurred first. Main Outcomes and Measures The first coprimary outcome was the composite of a new requirement for mechanical ventilation or death evaluated at 28 days. The second coprimary outcome was death at 28 days. Results A total of 1279 hospitalized patients (mean [SD] age, 61.8 [14.6] years; 449 [35.1%] women and 830 [64.9%] men) were randomized, including 639 patients in the usual care group and 640 patients in the colchicine group. Corticosteroids were used in 1171 patients (91.5%). The coprimary outcome of mechanical ventilation or 28-day death occurred in 160 patients (25.0%) in the colchicine group and 184 patients (28.8%) in the usual care group (hazard ratio [HR], 0.83; 95% CI, 0.67-1.02; P = .08). The second coprimary outcome, 28-day death, occurred in 131 patients (20.5%) in the colchicine group and 142 patients (22.2%) in the usual care group (HR, 0.88; 95% CI, 0.70-1.12). Diarrhea was the most frequent adverse effect of colchicine, reported in 68 patients (11.3%). Conclusions and Relevance This randomized clinical trial found that compared with usual care, colchicine did not significantly reduce mechanical ventilation or 28-day mortality in patients hospitalized with COVID-19 pneumonia.